2016
DOI: 10.1186/s12993-016-0100-5
|View full text |Cite
|
Sign up to set email alerts
|

Chronic cigarette smoking is linked with structural alterations in brain regions showing acute nicotinic drug-induced functional modulations

Abstract: BackgroundWhereas acute nicotine administration alters brain function which may, in turn, contribute to enhanced attention and performance, chronic cigarette smoking is linked with regional brain atrophy and poorer cognition. However, results from structural magnetic resonance imaging (MRI) studies comparing smokers versus nonsmokers have been inconsistent and measures of gray matter possess limited ability to inform functional relations or behavioral implications. The purpose of this study was to address thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
60
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(75 citation statements)
references
References 111 publications
11
60
0
4
Order By: Relevance
“…Analogous results were observed in behavioral addictions, including IA [45]. The abnormal OFC/vmPFC-cerebellar loop was also observed in various substance addictions, which was thought to contribute to craving for addictive substance [46,47]. As to IA, altered microstructure and function in the cerebellum, OFC, and vmPFC were also observed by previous neuroimaging studies [22,48,49].…”
Section: Neural Plasticitysupporting
confidence: 68%
“…Analogous results were observed in behavioral addictions, including IA [45]. The abnormal OFC/vmPFC-cerebellar loop was also observed in various substance addictions, which was thought to contribute to craving for addictive substance [46,47]. As to IA, altered microstructure and function in the cerebellum, OFC, and vmPFC were also observed by previous neuroimaging studies [22,48,49].…”
Section: Neural Plasticitysupporting
confidence: 68%
“…Taken together, both MAOA rs1137070 and smoking modulate the dopamine concentration in brain, which underlies the reinforcing properties of nicotine. Chronic nicotine exposure is associated with brain structural and functional alterations (Brody et al, 2004;Claus et al, 2013;Shen et al, 2016;Stoeckel et al, 2016;Sutherland et al, 2016). The susceptibility difference induced by genetic variation may also have its neural substrate, which presents before disease onset or interacts with long-term drug use.…”
Section: Introductionmentioning
confidence: 99%
“…Karama and colleagues 18 analyzed MRI data from 504 individuals at 73 years of age and reported diffuse accelerated cortical thinning, especially in prefrontal areas, in smokers compared with nonsmokers, and dose-dependent correlations between the amount smoked and the extent of cortical thinning in some regions. In a recent meta-analysis of structural MRI data, Sutherland and colleagues 19 reported smoking to be associated with structural decreases in the insula, cerebellum, parahippocampus, prefrontal cortex and thalamus. Structural alter ations, including decreases in grey matter volume of various brain structures and increased fractional anisotropy in diffusion tensor imaging studies, have been found not only in older smokers, but also in smokers younger than 30 years of age.…”
Section: J Psychiatry Neurosci 2017;42(3)mentioning
confidence: 99%